Structural analysis of an active beam - Syed Mohamed Ali, Jaffar; Khan, Md. Raisuddin; Hamid, Md.Tarique (IIUM Press, 2011)
An adaptive beam model of anisotropically actuated beam is formulated to determine the displacement and twist actuation capabilities of anisotropic piezoelectric actuators as related to the potential application for the helicopter blade control. The chosen beam has been modeled in ANSYS. Some existing results on piezoeletric actuators with different combinations and lay-ups were verified.